Remember Me Film Festival : An Education Efforts to Increase Dementia Awareness in Young Generations - Yuda Turana; D. Y. Suharya; Dian Purnomo (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
The role of film as one of the effective educational media is fundamental, especially in promoting awareness of the early symptoms of Alzheimer's disease. In Indonesia, there have not been many productions that specifically aim to escalate knowledge and awareness of Alzheimer's disease. The purpose of this activity was to increase public awareness of dementia and Alzheimer's, promote prevention and dementia risk reduction, produce short films on dementia and Alzheimer's with Indonesian cultural background as well as encouraging people toward elderly-friendly behavior. The event was held as a collaboration between FKIK Unika Atma Jaya, Alzheimer's Indonesia, and Eagle Institute titled Remember Me Film Festival (RMFF). In disseminating the information, The RMFF activities were publicized via YouTube and mass media. The aims of this study was to discuss the Remember Me Film Festival (RMFF) meetings as part of the tridharma institutions (community service), evaluation of benefits to the community, and qualitative assessment of the contents of dementia research for viewers on social media (YouTube) at three time points of observation (1 year after being downloaded on YouTube). The results of RMFF revealed that for each point of observation there was an increase in the number of views from September 2017 to October 2018. The RMFF activity can thus be employed as a model of increasing health promotion using digital/online platform for the younger generation.